Referencing technique for phase detection in Eddy current evaluation - Nadzri, N. A.; Mohd Mawardi, Saari; Zaini, M. A. H. P.; Aziz, Z. A. (Faculty Mechanical Engineering, UMP, 2021)
This paper presents an eddy current testing (ECT) method with a different type of referencing technique for crack detection in carbon steel plate by using two Anisotropic Magnet Resistance (AMR) sensors to detect and evaluate the artificial cracks and to study the output signal's characteristics of each technique. The experiment setup of the magnetic scanning device and the measurement mode is included. Based on these three techniques that have been used, it shown that differential technique with the condition of the required reference signal must be dynamic from one point to one point was the best way to implement in the ECT method. The line scanning results indicate that performing these three techniques can be used to estimate the position of the slits, however, for 2-D mapping, it is shown that the differential technique is a preferable technique where it can remove the noise response, and at the same time, it generates a clear image of the crack. It is predicted that the developed ECT probe using a differential technique can be used as a technique to estimate the characteristic of defects in a metal plate.